RESILIENSI TRADISI MANTU BUBAK DALAM KONTEKS MODERNITAS: STUDI PADA MASYARAKAT KOTA MADIUN, JAWA TIMUR - Muhammad Hanif; Sumarsih Sumarsih; Atik Puji A; Anita Indriani (Yayasan Literasi Sains Indonesia, 2026)
This study aims to analyze the cultural resilience of the Mantu Bubak tradition in the Madiun City community, East Java, in facing the pressures of modernity. This study uses a qualitative approach with a case study design and an ethnographic perspective. Data were collected through participant observation, in-depth interviews, and documentation, then analyzed using thematic analysis. The results show that the Mantu Bubak tradition persists through a process of cultural negotiation reflected in three main dimensions: adaptation, transformation, and continuity. Adaptation is seen in changes in location and implementation mechanisms to adapt to the context of urban society. Transformation is demonstrated through the reinterpretation of the meaning and aesthetics of the tradition, while continuity is reflected in the persistence of core values such as togetherness, mutual cooperation, and the practice of sharing. This study shows that the sustainability of a tradition does not depend on the integrity of a rigid ritual form, but rather on the community's ability to dynamically adapt the practices and meanings of the tradition. Unlike previous studies that tend to emphasize the ritual aspect or symbolic meaning in general, this study highlights how urban communities negotiate social space and cultural symbols in maintaining traditional identity. These findings confirm that cultural resilience is a dynamic process that allows traditions to remain relevant amidst social change.